GAMBARAN KECEMASAN MASYARAKAT DESA X DI SIDOARJO PASCA BENCANA ANGIN PUTING BELIUNG - Giza Rotul Nikmah; Hazim Hazim (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Residents of Kedondong Village, Sidoarjo Regency experienced psychological problems due to the occurrence of tornado natural disasters that could damage residents' homes and other infrastructure, the occurrence of these natural disasters could cause anxiety to residents and children of Kedondong Village. Therefore, an initial treatment is needed in order to reduce the impact of anxiety that occurs with an intervention, namely with Psychological First Aid (PFA). This study used qualitative descriptive methods and then to obtain information on the impact of the disaster event was carried out by observation and interviews on village officials and residents of Kedondong village, Sidoarjo regency. The results of this study residents who previously experienced an anxiety due to the tornado disaster are now gradually improving after being given the application of Psychological First Aid (PFA).